Nocebo effect in inhaler use: Patients' beliefs and treatment adherence - Eduardo Garcia-Pachon; María J. Soler-Sempere; Sandra Ruiz-Alcaraz; Ana Ibarra-Macia; Marina Belendez-Vazquez (Exploratory Research in Clinical and Social Pharmacy)
Background: The nocebo effect refers to the experience of nonspecific symptoms attributed to medical treatments, which cannot be explained by the pharmacological effects of the medication. This phenomenon, where symptoms are incorrectly linked to a treatment, can have significant implications for treatment adherence and may lead to increased patient demand for medical assistance. Objective: To ascertain the frequency and types of nocebo effects attributed to inhaler use, along with the associated factors. Methods: An interview was conducted to inquire about adverse effects attributed to inhalers. Additionally, questionnaires on beliefs about medications, general and specific to inhalers, and perceived sensitivity to medications scale were administered. Adherence to inhaled therapy was established using the inhaler adherence test and the electronic prescription refill rate at the pharmacy. Results: A total of 134 patients were included, among whom 21 (16 %) attributed symptoms to inhalers that were considered to be due to the nocebo effect. Patients experiencing nocebo-related symptoms exhibited greater concerns about using inhalers, heightened sensitivity to drug effects, and lower therapeutic adherence. Conclusions: A significant proportion of patients receiving inhaler therapy associate negative symptoms that are not reasonably attributable to the inhalers themselves. Patients prone to attributing nonspecific symptoms to inhalers differ in their beliefs about medications and exhibit lower therapeutic adherence compared to others.